2015
DOI: 10.12776/qip.v19i2.609
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between Lean Leaders and healthy co-workers?

Abstract: Purpose: The purpose of this article is to examine the relationship between Lean values, Lean leadership and perceived co-worker health both from an empirical and theoretical perspective. Methodology/Approach:A questionnaire used at a Swedish municipality that has been working with quality improvements for 20 years and with Lean for seven years was analyzed. 841 co-workers answered the questionnaire which had been designed and pre-tested to measure the presence of a number of Lean values and Lean leadership as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…They state that it seems that the effect is more a result from the implementation process and the context in which lean is being implemented (Hasle et al, 2012). Bäckström and Ingelsson (2015) found a positive correlation between the co-workers' perception of their health and lean leadership and lean values in their study at a municipality. When examining QM in relation to lean and from both a worker health and safety and operational performance perspective, Longoni et al (2013) conclude that QM needs to be further explored in relation to the wider lean context.…”
Section: Qm Initiatives and Co-worker Healthmentioning
confidence: 99%
“…They state that it seems that the effect is more a result from the implementation process and the context in which lean is being implemented (Hasle et al, 2012). Bäckström and Ingelsson (2015) found a positive correlation between the co-workers' perception of their health and lean leadership and lean values in their study at a municipality. When examining QM in relation to lean and from both a worker health and safety and operational performance perspective, Longoni et al (2013) conclude that QM needs to be further explored in relation to the wider lean context.…”
Section: Qm Initiatives and Co-worker Healthmentioning
confidence: 99%
“…Secondly, the results were analysed in order to examine the relationship between Lean values and perceived co-worker health and the result was recently presented in Bäckström and Ingelsson (2015). The mean value and the standard deviation of each variable was also calculated.…”
Section: Methodology and Case Descriptionmentioning
confidence: 99%
“…Lean can have both positive and negative effects on the working environment and it depends on how it is practiced within the organisation (Hasle, et al, 2012). Recent research has found positive correlations between Lean values, Lean Leadership and co-workers' perception of their health (Bäckström and Ingelsson, 2015) but Lean has also been criticized for impacting negatively on the working environment. Research of the use of Appreciative Inquiry has increased drastically in recent years especially in public organisations (see for instance Carter, 2006), but research combining Lean and Appreciative Inquiry is rather rare (Hansen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…LL is a meticulous system used for the sustainable implementation and continuous improvement of Lean Production [6]. It describes the cooperation of company officials and leaders in their mutual pursuit of perfection [7].…”
Section: Literature Reviewmentioning
confidence: 99%